STUDENTS’ READING ABILITY OF NARRATIVE TEXTS (A STUDY AT SMAN 2 VII KOTO SUNGAI SARIAK OF PADANG PARIAMAN REGENCY) - Septy, Adzanil Prima; Harmaini, Fitrina; Utami, Lara Diah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This descriptive research aimed to assess the reading comprehension abilities of students regarding narrative texts at SMAN 2 VII Koto Sungai Sariak of Padang Pariaman regency. The study utilized stratified cluster random sampling to select a sample of 60 students and collected data through a reading test. The study revealed that the students' overall ability to read narrative texts was low. Specifically, 65% of the students struggled to comprehend narrative texts. Within the narrative text components, 51% of students had difficulty understanding the orientation, 63% had trouble with the complication, 55% struggled with the resolution, and 67% found the reorientation challenging. Despite these difficulties, the study highlighted issues with students' learning motivation and the effectiveness of teaching strategies within the context of the current curriculum implementation, Kurikulum Merdeka. The study suggests that English teachers should revise narrative text lesson materials and teaching strategies to enhance student engagement and motivation, particularly for the Kurikulum Merdeka program. It also recommends vocabulary development and investigating students' reading difficulties for effective interventions.